Molecular design of a therapeutic LSD analogue with reduced hallucinogenic potential - Jeremy R. Tuck; Lee E. Dunlap; Yara A. Khatib; Cassandra J. Hatzipantelis; Sammy Weiser Novak; Rachel M. Rahn; Alexis R. Davis; Adam Mosswood; Anna M. M. Vernier; Ethan M. Fenton; Isak K. Aarrestad; Robert J. Tombari; et al. (Proceedings of the National Academy of Sciences, 2025)
Decreased dendritic spine density in the cortex is a key pathological feature of neuropsychiatric diseases including depression, addiction, and schizophrenia (SCZ). Psychedelics possess a remarkable ability to promote cortical neuron growth and increase spine density; however, these compounds are contraindicated for patients with SCZ or a family history of psychosis. Here, we report the molecular design and de novo total synthesis of (+)-JRT, a structural analogue of lysergic acid diethylamide (LSD) with lower hallucinogenic potential and potent neuroplasticity-promoting properties. In addition to promoting spinogenesis in the cortex, (+)-JRT produces therapeutic effects in behavioral assays relevant to depression and cognition without exacerbating behavioral and gene expression signatures relevant to psychosis. This work underscores the potential of nonhallucinogenic psychoplastogens for treating diseases where the use of psychedelics presents significant safety concerns.